Table of Content - - (Journal of engineering sciences and information technology, 2025)
Table of Content:1. Challenges of implementing sustainable design and construction in building projects in kuwaitEng. Mohamed Ezzat Elnakhely,  Eng. Faisal Sadeq Alhawaj2. Leading Innovation Using AI in Higher Education Institutions: A Systematic Review to Analyze Strategies and ChallengesMr. Sami Munahi Almeqati3. Transformation of Safety Management in Mega Projects: Exploring the Impact of Smart Technology and Digitization on Performance and Safety in Saudi ArabiaDr. Mohammad Abdullah Barnawy ,Dr. Samiyah Rafan Althaqafy ,Mr. Faris Omar Batawi4. Improvement of Cooperative Spectrum Sensing in Rayleigh Fading and AWGN Environments for Cognitive Radio NetworksEng. Rayan Abdelazeem Haboub, Prof. Khalid Hamid Bilal5. Sustainable Community participation in heritage conservation plans: A systematic literature review comparing international frameworks with practicesEng. Ghada Fathy Abdel-Fattah, Prof. Muhammad Ibrahem Gabr, Co-Prof. Mohamed Ezzeldin
Keywords: Journal of Engineering Sciences and Information Technology